2017
DOI: 10.3389/fpsyt.2017.00055
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Trauma and Stressful Life Events among Individuals at Clinical High Risk for Psychosis: A Review

Abstract: The experience of childhood trauma (CT) and stressful life events (SLEs) is associated with subsequent development of a variety of mental health conditions, including psychotic illness. Recent research identifying adolescents and young adults at clinical high risk (CHR) for psychosis allows for prospective evaluation of the impact of trauma and adverse life events on psychosis onset and other outcomes, addressing etiological questions that cannot be answered in studies of fully psychotic or non-clinical popula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
139
1
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 152 publications
(155 citation statements)
references
References 160 publications
(253 reference statements)
11
139
1
4
Order By: Relevance
“…Consistent with research linking trauma with psychosis vulnerability (Mayo et al, ), 90% of delinquent girls in the present study reported exposure to ≥10 adversity types, including sexual assault (>60%) which is the most common childhood trauma associated with transition to psychosis (Bechdolf et al, ; Thompson et al, ). Nearly 82% of girls met moderate to extreme levels of PTSD in their lifetime, and trauma exposure types were specifically associated with “relational” psychotic‐spectrum symptoms (hypersensitivity, paranoid, schizoid) likely to disrupt social outcomes.…”
Section: Discussionsupporting
confidence: 87%
See 4 more Smart Citations
“…Consistent with research linking trauma with psychosis vulnerability (Mayo et al, ), 90% of delinquent girls in the present study reported exposure to ≥10 adversity types, including sexual assault (>60%) which is the most common childhood trauma associated with transition to psychosis (Bechdolf et al, ; Thompson et al, ). Nearly 82% of girls met moderate to extreme levels of PTSD in their lifetime, and trauma exposure types were specifically associated with “relational” psychotic‐spectrum symptoms (hypersensitivity, paranoid, schizoid) likely to disrupt social outcomes.…”
Section: Discussionsupporting
confidence: 87%
“…The SCI‐PSY (Sbrana et al, ) is a 164‐item structured interview that includes total, domain and subdomain scores derived from dichotomous (0 = no, 1 = yes) lifetime classic positive and negative symptoms, prodromal/soft signs and personal characteristics (Appendix S1). The spectrum‐model has established reliability and validity with controls and patient groups as well as our delinquent girls (Appendix S1), and is consistent with a psychosis‐continuum supported by a wide literature (Cuesta & Peralta, ; Linscott & Van Os, ; Mayo et al, ; Rossi & Daneluzzo, ; Van Os et al, ). While not intended to be diagnostic, the SCI‐PSY captures treatment‐relevant symptoms, with items reflecting sensitivity, specificity, and predictive values for psychotic‐like experiences (hallucinations, paranoid thoughts) when comparing screens to clinical interviews (Kelleher, Harley, Murtagh, & Cannon, ).…”
Section: Methodssupporting
confidence: 73%
See 3 more Smart Citations